The Oxford handbook of corporate social responsibility - Crane, Andrew , 1968- (Oxford handbooks, 2008)
Business schools, the media, the corporate sector, governments, and non-governmental organizations have all begun to pay more attention to issues of Corporate Social Responsibility (CSR) in recent years. These issues encompass broad questions about the changing relationship between business, society and government, environmental issues, corporate governance, the social and ethical dimensions of management, globalization, stakeholder debates, shareholder and consumer activism, changing political systems and values, and the ways in which corporations can respond to new social imperatives. This Oxford Handbook is an authoritative review of the academic research that has both prompted, and responded to, these issues. Bringing together leading experts in the area, it provides clear thinking and new perspectives on CSR and the debates around it